Text As a Product of Language Communication and Pragmatic Descriptions of Verbal Communication - Berdiyorova Rahima Karimovna (Genius Journals, 2023)
Mutual understanding of the dialogue participants, their communicative and linguistic competence, knowledge of the external conditions of the speech relationship is the basis of achieving pragmatic results.A certain communicative situation, a certain pragmatic function of the text predetermines the character of the language formation of the text. Phraseological units, whose pragmatic function is usually manifested, realize their original pragmatic possibilities and acquire new ones, allowing to have a more active influence on the addressee.
Keywords: Semantic-communicative; Text analysis; communicative text